Method for preparing solid electrolyte and solid electrolyte

By crushing and mixing sulfide-based solid electrolyte raw materials, compressing them into pellets and sintering, the impurity problem during the preparation process is solved, and the ion conductivity and physical properties of the electrolyte are significantly improved.

CN119631214APending Publication Date: 2025-03-14LG CHEM LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380058746.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-16
Filing Date
2023-09-18
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing sulfide-based solid electrolytes have impurities problems during the preparation process, resulting in a decrease in ion conductivity.

Method used

By pulverizing the sulfide-based solid electrolyte raw material and mixing it, compressing it into a pellet form, and then sintering is carried out, and the impurities are reduced by pulverizing.

Benefits of technology

It effectively improves the reactivity of the raw materials, contains almost no impurities, and improves the ion conductivity and physical properties of the sulfide-based solid electrolyte.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention relates to a method for preparing a sulfide-based solid electrolyte and a sulfide-based solid electrolyte prepared thereby, the method comprising the steps of: (A) preparing a reaction mixture by pulverizing each sulfide-based solid electrolyte raw material and mixing the pulverized raw materials; (B) compressing the reaction mixture into a pellet form; and (C) preparing a sintered product by sintering the reaction mixture in the pellet form.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority to and the benefit of Korean Patent Application No. 10-2022-0117225, filed on September 16, 2022, and No. 10-2022-0117226, filed on September 16, 2022, the disclosures of which are incorporated herein by reference. Technical Field

[0003] The present invention relates to a method for preparing a sulfide-based solid electrolyte and the solid electrolyte prepared thereby. Background Art

[0004] An all-solid-state battery is a battery that uses solids instead of liquid electrolytes to fill the positive and negative electrodes of conventional lithium secondary batteries. It has attracted much attention as the next generation of batteries because it has a higher energy density than conventional batteries and is safe because there is no risk of explosion. The solid electrolyte used in an all-solid-state battery is a solid material that can conduct lithium ions in the battery, wherein it has a high ion conductivity comparable to the ion conductivity of the electrolyte currently used in lithium secondary batteries. The core materials that constitute the solid electrolyte include polymers, sulfides or oxides, and among them, sulfide-based solid electrolytes with high ductility and ion conductivity are evaluated as suitable for preparing large batteries with high capacity.

[0005] The sulfide-based solid electrolyte is usually prepared by simply mixing raw materials and then heat-treating the mixture. In this case, since not only unreacted unreacted products but also side reaction products, i.e., impurities, are present in the raw materials, there is a problem that the ion conductivity of the sulfide-based solid electrolyte is reduced.

[0006] In particular, in the case where it deviates from the basic composition of Li6PS5Ha (Ha: chlorine (Cl), bromine (Br), iodine (I)), there is a problem that the impurity content further increases due to structural instability. Summary of the invention

[0007] Technical issues

[0008] One aspect of the present invention provides a method for preparing a sulfide-based solid electrolyte, which improves the reactivity of raw materials so that the obtained sulfide-based solid electrolyte contains almost no impurities, and a sulfide-based solid electrolyte prepared thereby.

[0009] Technical Solution

[0010] The present invention provides a method for preparing a sulfide-based solid electrolyte and the sulfide-based solid electrolyte.

[0011] (1) The present invention provides a method for preparing a sulfide-based solid electrolyte, the method comprising the following steps: (A) preparing a reaction mixture by pulverizing respective sulfide-based solid electrolyte raw materials and mixing the pulverized raw materials; (B) compressing the reaction mixture into a pellet form; and (C) preparing a sintered product by sintering the pellet-shaped reaction mixture.

[0012] (2) The present invention provides the method described in (1) above, wherein the sulfide-based solid electrolyte raw material comprises (i) a lithium-containing raw material, (ii) a phosphorus-containing raw material, (iii) a sulfur-containing raw material, and optionally (iv) at least one selected from a halogen-containing raw material, an M-containing raw material (M is at least one selected from silicon (Si) and germanium (Ge)) and a N-containing raw material (N is at least one selected from tin (Sn), antimony (Sb), aluminum (Al), gallium (Ga), zinc (Zn), zirconium (Zr), indium (In) and copper (Cu)).

[0013] (3) The present invention provides the method described in (1) or (2) above, wherein the pulverization in step (A) is performed by a ball mill using two or more balls having different diameters.

[0014] (4) The present invention provides the method described in (3) above, wherein during the pulverization in step (A), the diameter of the balls is 1 mm, 3 mm or 5 mm.

[0015] (5) The present invention provides the method described in any one of (1) to (4) above, wherein the pulverization in step (A) is performed at a rotation speed of 500 rpm to 800 rpm.

[0016] (6) The present invention provides the method according to any one of (1) to (5) above, wherein the mixing in step (A) is performed by mixing in a ball mill using two or more balls having different diameters.

[0017] (7) The present invention provides the method described in (6) above, wherein during the mixing in step (A), the diameter of the balls is 1 mm, 3 mm, 5 mm or 10 mm.

[0018] (8) The present invention provides the method described in any one of (1) to (7) above, wherein the mixing in step (A) is performed at a rotation speed of 200 rpm to 500 rpm.

[0019] (9) The present invention provides a method as described in any one of (2) to (8) above, wherein (iv) the halogen-containing raw material comprises a chlorine-containing raw material and a bromine-containing raw material, and the ratio of the number of moles of halogen contained in the reaction mixture to the total number of moles of phosphorus, M and N is in the range of 1.1 to 1.5.

[0020] (10) The present invention provides the method according to any one of (1) to (9) above, wherein during the preparation of the reaction mixture, a non-reactive solvent having a relative polarity of 0 to 0.15 relative to water is further mixed.

[0021] (11) The present invention provides the method described in (10) above, wherein the non-reactive solvent is mixed in an amount of 2.5 wt % to 5.0 wt % based on the total amount of the sulfide-based solid electrolyte raw material.

[0022] (12) The present invention provides the method according to any one of (1) to (11) above, wherein the compressing in the step (B) is performed at a pressure of 50 MPa to 400 MPa.

[0023] (13) The present invention provides the method described in any one of (1) to (12) above, wherein the sintering is performed at a temperature of 350°C to 600°C.

[0024] (14) The present invention provides the method described in any one of (1) to (13) above, wherein the method further comprises the following step: (D) pulverizing the sintered product.

[0025] (15) The present invention provides the method described in (14) above, wherein the pulverizing in step (D) includes mortar pulverizing the sintered product, and ball mill pulverizing the mortar pulverized sintered product using two or more balls with different diameters.

[0026] (16) The present invention provides the method described in (15) above, wherein during the pulverizing in the step (D), the diameter of the balls is 1 mm, 3 mm, 5 mm or 10 mm.

[0027] (17) The present invention provides the method described in any one of (14) to (16) above, wherein the pulverization in the step (D) is performed at a rotation speed of 100 rpm to 500 rpm.

[0028] (18) The present invention provides a sulfide-based solid electrolyte having a composition represented by Formula 1 and having a total impurity content of 3 wt % or less.

[0029] [Formula 1]

[0030] Li 7-(x+y)+((a×(5-p))+(b×(5-q))) P1-(a+b) M a N b S 6-(x+y) Cl x Br y

[0031] In Formula 1,

[0032] M is at least one selected from silicon (Si) and germanium (Ge),

[0033] N is at least one selected from tin (Sn), antimony (Sb), aluminum (Al), gallium (Ga), zinc (Zn), zirconium (Zr), indium (In), and copper (Cu),

[0034] p is the oxidation number of M, q is the oxidation number of N, and

[0035] 0.1 ≤ x ≤ 1.4, 0.1 ≤ y ≤ 1.4, 1.1 < x + y ≤ 1.5, 0 ≤ a ≤ 0.5 and 0 ≤ b ≤ 0.2.

[0036] (19) The present invention provides the sulfide-based solid electrolyte of the above (18), wherein the sulfide-based solid electrolyte has an ionic conductivity of 4.0 mS / cm or more.

[0037] (20) The present invention provides the sulfide-based solid electrolyte of the above (18) or (19), wherein the sulfide-based solid electrolyte has an electronic conductivity of 1.0×10 -9 mS / cm to 1.0×10 -4 mS / cm.

[0038] (21) The present invention provides the sulfide-based solid electrolyte of any one of the above (18) to (20), wherein the sulfide-based solid electrolyte has an average particle size (D 50 ) of 1.0 μm to 5.0 μm.

[0039] Beneficial Effects

[0040] Regarding the method for preparing a sulfide-based solid electrolyte according to the present invention, it can not only prevent the adhesion of raw materials but also improve the reactivity of raw materials through the following steps: pre-crushing each raw material and then mixing them to prepare a reaction mixture, compressing the reaction mixture into a pellet form, and then sintering the reaction mixture in pellet form.

[0041] Therefore, regarding the sulfide-based solid electrolyte prepared by the method for preparing a sulfide-based solid electrolyte according to the present invention, since there are almost no impurities, there is an advantage of excellent physical properties (such as ionic conductivity). Detailed Description

[0042] Hereinafter, the present invention will be described in more detail so that the present invention can be more clearly understood. In this case, it should be understood that the words or terms used in this specification and claims should not be interpreted as the meanings defined in commonly used dictionaries, and it should be further understood that the words or terms should be interpreted as having meanings consistent with their meanings in the context of the prior art and the technical ideas of the present invention based on the principle that the inventors can appropriately define the meanings of the words or terms to best explain the present invention.

[0043] The terms used herein are for the purpose of describing specific example embodiments only and are not intended to limit the present invention. In the present specification, unless otherwise specified, terms in the singular form may include plural forms.

[0044] It should be further understood that when used in this specification, the terms "include", "comprises" or "has" clarify the existence of the described features, numbers, steps, elements or their combinations, but do not exclude the existence or addition of one or more other features, numbers, steps, elements or their combinations.

[0045] In this manual, "D n " represents the particle size at n% based on the volume cumulative distribution of particle size. That is, D 50 It is the particle size at which the volume cumulative distribution of particle size is 50%, D 90 It is the particle size at 90% of the volume cumulative distribution of particle size, D 10 It is the particle size at which the volume cumulative distribution of particle size reaches 10%. n It can be measured by using a laser diffraction method. Specifically, after the measurement target powder is dispersed in a dispersion medium (xylene), the dispersion medium is introduced into a commercial laser diffraction particle size measuring instrument (e.g., Mastersizer 3000 of Malvern Panalytical Ltd.) and the particle size distribution is calculated by measuring the difference in diffraction patterns caused by the particle size when the particles pass through the laser beam. 10 , D 50 and D 90 It can be measured by calculating the particle diameters at 10%, 50%, and 90% according to the volume cumulative distribution of the particle diameters using a measuring instrument.

[0046] In this specification, the relative polarity of a solvent with respect to water means the polarity of the solvent when the polarity of water is 1. For example, the relative polarity of xylene with respect to water is 0.074, the relative polarity of toluene with respect to water is 0.099, and the relative polarity of hexane with respect to water is 0.009.

[0047] The expression "all-solid-state battery" used in this specification means a battery in which all components of the battery are solid, which is distinguished from a liquid electrolyte secondary battery using a liquid electrolyte (such as an electrolyte), and a gel-type polymer secondary battery that uses a polymer electrolyte instead of a separator while also using a liquid electrolyte.

[0048] Method for preparing sulfide-based solid electrolyte

[0049] The method for preparing a sulfide-based solid electrolyte according to the present invention comprises the following steps: (A) preparing a reaction mixture by pulverizing respective sulfide-based solid electrolyte raw materials and mixing the pulverized raw materials; (B) compressing the reaction mixture into a pellet form; and (C) preparing a sintered product by sintering the pellet-shaped reaction mixture.

[0050] The method for preparing a sulfide-based solid electrolyte according to the present invention may further include the following step: (D) pulverizing the sintered product.

[0051] Hereinafter, each step of the method for preparing a sulfide-based solid electrolyte according to the present invention will be described.

[0052] Step (A)

[0053] The step (A) is a step of preparing a reaction mixture by pulverizing sulfide-based solid electrolyte raw materials independently and then mixing them.

[0054] According to the present invention, the sulfide-based solid electrolyte raw material may include (i) a lithium-containing raw material, (ii) a phosphorus-containing raw material, (iii) a sulfur-containing raw material, and optionally (iv) at least one selected from a halogen-containing raw material, an M-containing raw material (M is at least one selected from silicon (Si) and germanium (Ge)) and a N-containing raw material (N is at least one selected from tin (Sn), antimony (Sb), aluminum (Al), gallium (Ga), zinc (Zn), zirconium (Zr), indium (In) and copper (Cu)). Specifically, the sulfide-based solid electrolyte raw material may be (i) a lithium-containing raw material, (ii) a phosphorus-containing raw material, (iii) a sulfur-containing raw material, and optionally (iv) at least one selected from a halogen-containing raw material, an M-containing raw material (M is at least one selected from Si and Ge) and a N-containing raw material (N is at least one selected from Sn, Sb, Al, Ga, Zn, Zr, In and Cu).

[0055] Step (A) may specifically be a step of preparing a reaction mixture by ball milling the following materials independently using a planetary ball mill apparatus, and then mixing them: (i) a lithium-containing raw material, (ii) a phosphorus-containing raw material, (iii) a sulfur-containing raw material, and optionally (iv) at least one selected from a halogen-containing raw material, an M-containing raw material (M is at least one selected from Si and Ge) and a N-containing raw material (N is at least one selected from Sn, Sb, Al, Ga, Zn, Zr, In and Cu). For example, before mixing Li2S and P2S5 and optionally at least one selected from LiCl, LiBr, SiS2 and SnS2, each may be firstly pulverized using a zirconia ball and then mixed to prepare a reaction mixture. In this case, the surface area of ​​the raw material can be increased to improve reactivity, and impurities are almost absent in the resulting sulfide-based solid electrolyte. In the case where the raw materials are mixed without first pulverizing and then a sulfide-based solid electrolyte is prepared, the raw materials may adhere while being unevenly mixed, and there is a problem of residual high content of impurities due to partial unevenness of the composition. That is, since some raw materials cause adhesion, in a case where each raw material is first pulverized and then mixed, rather than in a case where the raw materials used in preparing a solid electrolyte are mixed without pulverizing, the particle size of the raw materials can be adjusted to be small and the reactivity can be improved.

[0056] For reference, when the raw materials are mixed during the preparation process of the sulfide-based solid electrolyte, since the sulfur-containing raw materials adhere to the wall of the pulverizer (e.g., a ball mill container), an adhesion phenomenon occurs and impurities are formed, and there is a problem that the ion conductivity may be reduced due to sulfur deficiency. In the present invention, as described above, the adhesion phenomenon can be effectively suppressed by pre-pulverizing the raw materials and then mixing them, and the ion conductivity of the obtained solid electrolyte can also be improved.

[0057] According to the present invention, (i) the lithium-containing raw material may be Li2S, Li2S2, Li2S4, Li2S6, LiCl, LiBr, Li, Li3PS4, LiOH, Li2CO3 or a combination thereof, but is not limited thereto. (i) The lithium-containing raw material may be mixed in an amount such that the resulting sulfide-based solid electrolyte has a composition represented by Formula 1 described herein.

[0058] According to the present invention, (ii) the phosphorus-containing raw material may be P2S5, Li3PS4 or a combination thereof, but is not limited thereto. (ii) The phosphorus-containing raw material may be mixed in an amount such that the resulting sulfide-based solid electrolyte has a composition represented by Formula 1 described herein.

[0059] According to the present invention, (iii) the sulfur-containing raw material may be Li2S, Li2S2, Li2S4, Li2S6, S8, P2S5, Li3PS4 or a combination thereof, but is not limited thereto. (iii) The sulfur-containing raw material may be mixed in an amount such that the resulting sulfide-based solid electrolyte has a composition represented by Formula 1 described herein.

[0060] According to the present invention, the halogen-containing raw material may be LiCl (chlorine-containing raw material), LiBr (bromine-containing raw material) or a combination thereof, but is not limited thereto. The halogen-containing raw material may be mixed in an amount such that the resulting sulfide-based solid electrolyte has a composition represented by Formula 1 described herein.

[0061] According to the present invention, the M-containing raw material (M is at least one selected from Si and Ge) can be SiS2, SiCl4, SiBr4, Li 3.75 Si, Si3P4, GeS2, GeCl4, GeBr4, Li 3.75 Ge, Ge3P4 or a combination thereof, but not limited thereto. The M-containing raw material may be mixed in an amount such that the resulting sulfide-based solid electrolyte has a composition represented by Formula 1 described herein.

[0062] According to the present invention, the N-containing raw material (N is at least one selected from Sn, Sb, Al, Ga, Zn, Zr, In and Cu) can be NS q / 2 、NBr q 、NCl q 、N 3 / q P, NP or a combination thereof (q is the oxidation number of N). Specifically, the N-containing raw material may be SnS2, SnCl4, SnBr4, Sn 3 / 4 P, SbS 2.5 、SbCl5、SbBr5、SbP、AlS 1.5 、AlCl3、AlBr3、AlP、GaS 1.5 , GaCl3, GaBr3, GaP, ZnS, ZnCl2, ZnBr2, Zn 1.5 P, ZrS2, ZrCl4, ZrBr4, ZrP, InS 1.5 ,InCl3,InBr3,InP,CuS,CuCl2,CuBr2,Cu 1.5 The N-containing raw material may be mixed in an amount such that the resulting sulfide-based solid electrolyte has a composition represented by Formula 1 described herein.

[0063] In the case where the reaction mixture contains an M-containing raw material (M is at least one selected from Si and Ge) and a N-containing raw material (N is at least one selected from Sn, Sb, Al, Ga, Zn, Zr, In and Cu), since the obtained sulfide-based solid electrolyte is doped with M and N, the ion conductivity and moisture stability can be further improved.

[0064] According to the present invention, the pulverization in step (A) may be a ball mill pulverization using two or more balls having different diameters. In the case where two or more balls having different diameters are used for pulverization, all particles may be uniformly pulverized into fine powder. The material of the ball may be the same material as that of the ball mill container, and may be, for example, zirconium oxide, stainless steel, tungsten carbide or silicon nitride.

[0065] According to the present invention, when the crushing of step (A) is carried out using two or more balls with different diameters, the diameter of the ball can be 1 mm, 3 mm or 5 mm. The energy applied to the particle is determined by the diameter of the ball, wherein, in the case where the diameter of the ball used in the crushing of step (A) is 1 mm, 3 mm or 5 mm, all particles can be crushed uniformly without exception. That is, the ball with a relatively larger diameter can crush large particles due to relatively higher energy, and the ball with a relatively smaller diameter can further reduce the particle size of the raw material.

[0066] For example, the pulverization in step (A) can be performed using two or more zirconia balls with different diameters. More specifically, the pulverization in step (A) can be performed using zirconia balls with a diameter of 1 mm and zirconia balls with a diameter of 3 mm, so that the average particle size (D 50 ) is less than 1 μm.

[0067] According to the present invention, the pulverization of step (A) can be carried out at a rotation speed of 500 rpm to 800 rpm. Specifically, the pulverization of step (A) can be carried out at a rotation speed of more than 500 rpm, more than 510 rpm, more than 520 rpm, more than 530 rpm, more than 540 rpm, more than 550 rpm, more than 560 rpm, more than 570 rpm, more than 580 rpm, more than 590 rpm or more than 600 rpm, and less than 700 rpm, less than 710 rpm, less than 720 rpm, less than 730 rpm, less than 740 rpm, less than 750 rpm, less than 760 rpm, less than 770 rpm, less than 780 rpm, less than 790 rpm or less than 800 rpm. In this case, since a rotation speed higher than a specific level is ensured, it is easy to pulverize raw materials with the ball, thereby, the size of each raw material can be effectively reduced. The pulverization in the step (A) is to pulverize each raw material individually, and is preferably performed using balls having a smaller particle size at a higher rotation speed than the mixing in the step (A) in which the raw materials are mixed.

[0068] The mixing of step (A) can be performed by a ball mill using two or more balls having different diameters. In this case, the raw materials can be mixed more uniformly. The material of the balls can be the same as that of the ball mill container, and can be, for example, zirconium oxide, stainless steel, tungsten carbide or silicon nitride.

[0069] According to the present invention, in the case where the mixing of step (A) is performed using two or more balls having different diameters, the diameter of the balls may be 1 mm, 3 mm, 5 mm or 10 mm. Even if pre-crushing is performed, additional crushing occurs together during mixing, wherein, since among the raw materials to be mixed, raw materials having large particle sizes are mainly crushed by large diameter balls and raw materials having small particle sizes are mainly crushed by small diameter balls, there is an advantage in that the obtained particle sizes become uniform and mixing is also well achieved.

[0070] For example, the mixing in step (A) can be performed using two or more zirconia balls having different diameters. More specifically, the mixing in step (A) can be performed using zirconia balls having a diameter of 3 mm and zirconia balls having a diameter of 5 mm.

[0071] According to the present invention, the mixing of step (A) can be carried out at a rotation speed of 200 rpm to 500 rpm. Specifically, the mixing of step (A) can be carried out at a rotation speed of more than 200 rpm, more than 210 rpm, more than 220 rpm, more than 230 rpm, more than 240 rpm or more than 250 rpm, and less than 450 rpm, less than 460 rpm, less than 470 rpm, less than 480 rpm, less than 490 rpm or less than 500 rpm. Since the mixing of step (A) is a process of remixing each pulverized raw material, it is preferably carried out at a lower rotation speed compared to the pulverization of step (A), and in the case of mixing at a rotation speed within the above range, the mixing time can be shortened.

[0072] According to the present invention, the halogen-containing raw material comprises a chlorine-containing raw material and a bromine-containing raw material, and the ratio of the number of moles of the halogen contained in the reaction mixture to the total number of moles of phosphorus, M and N can be in the range of 1.1 to 1.5. The ratio of the number of moles of the halogen contained in the reaction mixture to the total number of moles of phosphorus, M and N can be specifically 1.10 or more, 1.15 or more, 1.20 or more, 1.25 or more, 1.30 or more or 1.40 or more, and can be 1.50 or less. In this case, since the degree of delocalization of sulfide ions and halogen ions increases, the empty space at the site where lithium ions can be located increases to promote lithium ion conduction, thereby having the advantage of high ion conductivity.

[0073] According to the present invention, during the preparation of the reaction mixture, a non-reactive solvent having a relative polarity of 0 to 0.15 relative to water may be further mixed. In this case, based on the total amount of the sulfide-based solid electrolyte raw material (e.g., (i) the lithium-containing raw material, (ii) the phosphorus-containing raw material, (iii) the sulfur-containing raw material, and optionally (iv) at least one selected from the halogen-containing raw material, the M-containing raw material (M is at least one selected from Si and Ge) and the N-containing raw material (N is at least one selected from Sn, Sb, Al, Ga, Zn, Zr, In and Cu), the non-reactive solvent may be mixed in an amount of 2.5 wt % to 5.0 wt %. That is, step (A) may be a step of preparing the reaction mixture by mixing the sulfide-based solid electrolyte raw material with a trace amount of the non-reactive solvent.

[0074] Since the sulfide-based solid electrolyte raw materials (for example, (i) the lithium-containing raw material, (ii) the phosphorus-containing raw material, (iii) the sulfur-containing raw material, and optionally (iv) the halogen-containing raw material and the M-containing raw material (M is at least one selected from Si and Ge)) are highly reactive to moisture, they may generate harmful gas hydrogen sulfide when exposed to air during the sulfide-based solid electrolyte preparation process, wherein the method for preparing a sulfide-based solid electrolyte according to the present invention can prevent the raw materials from being exposed to air by further mixing a non-reactive solvent.

[0075] In order to prevent the raw materials from being exposed to the air and at the same time not to have a chemical effect on the raw materials, the relative polarity of the non-reactive solvent relative to water can be 0 to 0.15, specifically 0 or more, and 0.13 or less, 0.135 or less, 0.14 or less, 0.145 or less, or 0.15 or less. In the case where the relative polarity of the non-reactive solvent relative to water is greater than 0.15, a side reaction may occur between the solvent and the raw materials.

[0076] The non-reactive solvent may be, for example, at least one selected from the group consisting of xylene, benzene, toluene, pentane, hexane, cyclohexane, and heptane, but is not limited thereto.

[0077] According to the present invention, based on the total amount of the sulfide-based solid electrolyte raw material, the non-reactive solvent can be mixed in an amount of 2.5% to 5.0% by weight. Specifically, based on the total amount of the raw material, the non-reactive solvent can be mixed with 2.5% by weight, 2.6% by weight, 2.7% by weight, 2.8% by weight, 2.9% by weight, or 3.0% by weight, and 4.0% by weight, 4.1% by weight, 4.2% by weight, 4.3% by weight, 4.4% by weight, 4.5% by weight, 4.6% by weight, 4.7% by weight, 4.8% by weight, 4.9% by weight, or 5.0% by weight. In this case, not only can the raw material be prevented from being exposed to the air, but also the adhesion of the raw material that may occur during the preparation process of the sulfide-based solid electrolyte can be prevented. It is desirable that the solid electrolyte has characteristics of low electron conductivity and high ion conductivity, wherein, in the case where the non-reactive solvent is mixed in an amount greater than 5.0 wt % based on the total amount of raw materials, since the residual amount of carbon generated from the non-reactive solvent increases, and the electron conductivity of the solid electrolyte after the drying process and the sintering process increases due to the residual amount of carbon, it may cause problems in the function of the solid electrolyte that must conduct only ions.

[0078] In the present invention, as described above, the adhesion phenomenon can be effectively suppressed by adding a trace amount of the non-reactive solvent and mixing together, and the ion conductivity of the resulting solid electrolyte can be improved.

[0079] The reaction mixture prepared by step (A) can be a reaction mixture in the form of a powder in which the raw material and the non-reactive solvent are uniformly mixed. Although the reaction mixture contains the non-reactive solvent, it only contains a trace amount, and thus, the reaction mixture can be in the form of a powder rather than a slurry. Therefore, the mixing of step (A) can be considered as dry mixing rather than wet mixing.

[0080] Before the step of processing the reaction mixture into a pellet form, a step of drying the reaction mixture in powder form may be further performed. This is to remove the non-reactive solvent remaining in the uniformly mixed reaction mixture, wherein vacuum drying, heat drying, or heat drying under vacuum conditions may be performed at room temperature to below 200° C. for 1 minute to 10 hours. Specifically, vacuum drying may be performed at a temperature of 80° C. for 1 hour using a vacuum oven.

[0081] Step (B)

[0082] Step (B) is a step of compressing the reaction mixture into a pellet form. For example, the reaction mixture can be pelletized by compressing with a press. In this case, since the raw materials contained in the reaction mixture are densified to increase the contact area between the particles, there is an advantage of improving the reactivity between the raw materials.

[0083] According to the present invention, the compression in step (B) may be performed at a pressure of 50 MPa to 400 MPa. Specifically, the compression can be carried out at a pressure of more than 50 MPa, more than 55 MPa, more than 60 MPa, more than 65 MPa, more than 70 MPa, more than 75 MPa, more than 80 MPa, more than 85 MPa, more than 90 MPa, more than 95 MPa or more than 100 MPa, and less than 200 MPa, less than 210 MPa, less than 220 MPa, less than 230 MPa, less than 240 MPa, less than 250 MPa, less than 260 MPa, less than 270 MPa, less than 280 MPa, less than 290 MPa, less than 300 MPa, less than 310 MPa, less than 320 MPa, less than 330 MPa, less than 340 MPa, less than 350 MPa, less than 360 MPa, less than 370 MPa, less than 380 MPa, less than 390 MPa or less than 400 MPa. In this case, since the shape of the pellets is well maintained even after the pellets are taken out of the mold, a more uniform product can be obtained.

[0084] Step (C)

[0085] Step (C) is a step of sintering the reaction mixture in the form of pellets.

[0086] According to the present invention, the sintering may be performed in an inert atmosphere to prevent side reactions with oxygen and moisture. For example, the sintering may be performed in an argon atmosphere, a nitrogen atmosphere, or a helium atmosphere.

[0087] According to the present invention, the sintering may be performed at a temperature of 350° C. to 600° C. More specifically, the sintering temperature may be 350° C. or higher, 360° C. or higher, 370° C. or higher, 380° C. or higher, 390° C. or higher, 400° C. or higher, 410° C. or higher, 420° C. or higher, 430° C. or higher, 440° C. or higher, or 450° C. or higher, and 550° C. or lower, 560° C. or lower, 570° C. or lower, 580° C. or lower, 590° C. or lower, or 600° C. or lower. In the case where the sintering temperature is within the above range, an argyrodite-type crystal structure may be formed.

[0088] The sintering temperature holding time may be in the range of 1 hour to 24 hours. In this case, the reaction energy is sufficient to reduce the content of impurities, prevent partial decomposition of the argyrodite-type crystal phase at high temperature, and prevent excessive increase in the particle size of the sulfide-based solid electrolyte powder.

[0089] In the case where the reaction mixture comprises the M-containing raw material and the N-containing raw material, the sintering temperature may preferably be 400° C. or more, 405° C. or more, 410° C. or more, 415° C. or more, or 420° C. or more, and may be 480° C. or less, 485° C. or less, 490° C. or less, 495° C. or less, or 500° C. or less. In the case where the argyrodite composition is doped with P-site ions, the sintering temperature may be affected, the formation of impurities may be further reduced within the above range, and the properties of the prepared solid electrolyte, such as ionic conductivity, may be excellent.

[0090] Step (D)

[0091] The method for preparing a sulfide-based solid electrolyte according to the present invention may further include the following step: (D) pulverizing the sintered product.

[0092] Step (D) is a step of controlling the particle size by pulverizing the sintered product subjected to step (C). The sintered pellets may be pulverized by manual pulverization using a mortar (mortar pulverization), and may be pulverized using a planetary ball mill apparatus.

[0093] According to the present invention, the pulverization in step (D) may be a ball mill pulverization using two or more balls having different diameters. In the case where two or more balls having different diameters are used for pulverization, all particles may be uniformly pulverized into fine powder. The material of the ball may be the same material as that of the ball mill container, and may be, for example, zirconium oxide, stainless steel, tungsten carbide or silicon nitride.

[0094] According to the present invention, when two or more balls with different diameters are used to crush the step (D), the diameter of the ball may be 1 mm, 3 mm or 5 mm. The energy applied to the particle is determined by the diameter of the ball, wherein the diameter of the ball used in the crushing of the step (D) is 1 mm, 3 mm or 5 mm, and the particles can be crushed uniformly. That is, the ball with a relatively larger diameter can crush large particles due to relatively higher energy, and the ball with a relatively smaller diameter can further reduce the particle size of the raw material.

[0095] For example, the pulverization in step (D) can be performed using two or more zirconia balls with different diameters. More specifically, the pulverization in step (D) can be performed using zirconia balls with a diameter of 1 mm and zirconia balls with a diameter of 3 mm, so that the average particle size (D 50 ) is in the range of 1.0 μm to 5.0 μm.

[0096] According to the present invention, the pulverization of the step (D) can be carried out at a rotating speed of 100 rpm to 500 rpm. Specifically, the pulverization of the step (D) can be carried out at more than 100 rpm, more than 110 rpm, more than 120 rpm, more than 130 rpm, more than 140 rpm, more than 150 rpm, more than 160 rpm, more than 170 rpm, more than 180 rpm, more than 190 rpm or more than 200 rpm, and less than 400 rpm, less than 410 rpm, less than 420 rpm, less than 430 rpm, less than 440 rpm, less than 450 rpm or less, less than 460 rpm, less than 470 rpm, less than 480 rpm, less than 490 rpm or less than 500 rpm. In this case, due to the appropriate adjustment of the pulverization energy, not only can the solid electrolyte with the desired particle size be prepared, but also the decomposition of the solid electrolyte can be prevented.

[0097] According to the present invention, in terms of high ionic conductivity and low reactivity with a lithium negative electrode, the obtained sulfide-based solid electrolyte may have a thiogermanate-type crystal structure. That the sulfide-based solid electrolyte has a thiogermanate-type crystal structure means that the sulfide-based solid electrolyte has at least a crystal phase of the thiogermanate-type structure as the main phase. In this case, the main phase refers to the phase with the largest total ratio with respect to the total amount of all crystal phases constituting the sulfide solid electrolyte. Therefore, based on the total crystal phases constituting the sulfide-based solid electrolyte, the content ratio of the crystal phase of the thiogermanate-type structure contained in the sulfide-based solid electrolyte is preferably 90% by weight or more, and may be more preferably 92% by weight or more, 95% by weight or more, and 97% by weight or more.

[0098] Furthermore, according to the present invention, the obtained sulfide-based solid electrolyte may have a composition represented by the following formula 1.

[0099] [Formula 1]

[0100] Li 7-(x+y)+((a×(5-p))+(b×(5-q))) P 1-(a+b) M a N b S 6-(x+y) Cl x Br y

[0101] In formula 1,

[0102] M is at least one selected from Si and Ge,

[0103] N is at least one selected from Sn, Sb, Al, Ga, Zn, Zr, In, and Cu,

[0104] p is the oxidation number of M, q is the oxidation number of N, and

[0105] 0.1 ≤ x ≤ 1.4, 0.1 ≤ y ≤ 1.4, 1.1 < x + y ≤ 1.5, 0 ≤ a ≤ 0.5 and 0 ≤ b ≤ 0.2.

[0106] Sulfide-based solid electrolytes

[0107] The present invention provides a sulfide-based solid electrolyte having a composition represented by the following formula 1 and having a total impurity content of 3% by weight or less. The sulfide-based solid electrolyte according to the present invention can be prepared according to the above method for preparing a sulfide-based solid electrolyte. Therefore, the total impurity content can be very small.

[0108] [Formula 1]

[0109] Li 7-(x+y)+((a×(5-p))+(b×(5-q))) P 1-(a+b) M a N b S 6-(x+y) Clx Br y

[0110] In Formula 1,

[0111] M is at least one selected from Si and Ge,

[0112] N is at least one selected from Sn, Sb, Al, Ga, Zn, Zr, In, and Cu,

[0113] p is the oxidation number of M, q is the oxidation number of N, and

[0114] 0.1 ≤ x ≤ 1.4, 0.1 ≤ y ≤ 1.4, 1.1 < x + y ≤ 1.5, 0 ≤ a ≤ 0.5 and 0 ≤ b ≤ 0.2.

[0115] According to the present invention, the sulfide-based solid electrolyte may have a thiogermanate crystal structure. In this case, there are advantages in terms of high ionic conductivity, stability in contact with lithium, and reproducibility of synthesis.

[0116] According to the present invention, when preparing the sulfide-based solid electrolyte, the impurities may include unreacted products and side reaction products that have not reacted, and specifically, the impurities may be Li2S, LiCl, LiBr, and Li4SiS4. That is, the total impurity content may be the total content of Li2S, LiCl, LiBr, and Li4SiS4 remaining in the sulfide-based solid electrolyte. The impurity content may be obtained by analyzing the X-ray diffraction (XRD) data of the sulfide-based solid electrolyte powder using the Rietveld refinement program, but the present invention is not limited thereto.

[0117] When the sulfide-based solid electrolyte according to the present invention has a composition represented by Formula 1, there is an advantage that the ionic conductivity increases, and at the same time, the distribution of lithium (Li) is affected due to the presence of highly disordered chlorine (Cl) and bromine (Br).

[0118] According to the present invention, when the sulfide-based solid electrolyte is doped with M, that is, when a in Formula 1 is greater than 0, the amount of Li present in the solid electrolyte increases, and due to the fact that the microstructure expands and the asymmetry increases, there is an advantage of improving the ionic conductivity. In addition, when the sulfide-based solid electrolyte is doped with N, that is, when b in Formula 1 is greater than 0, since a stronger bond is formed with sulfur (S), the loss of S caused by moisture, the collapse of the structure, and the resulting reduction in performance and stability can be reduced.

[0119] According to the present invention, x may be greater than 0.10, greater than 0.15, greater than 0.20, greater than 0.25, greater than 0.30, greater than 0.35, or greater than 0.40, and may be less than 1.0, less than 1.05, less than 1.10, less than 1.15, less than 1.20, less than 1.25, less than 1.30, less than 1.35, or less than 1.40.

[0120] According to the present invention, y may be greater than 0.1, greater than 0.15, greater than 0.20, greater than 0.25, greater than 0.30, greater than 0.35, greater than 0.40, greater than 0.45, or greater than 0.50, and may be less than 1.0, less than 1.05, less than 1.10, less than 1.15, less than 1.20, less than 1.25, less than 1.30, less than 1.35, or less than 1.40.

[0121] According to the present invention, x+y may be 1.10 or more, 1.15 or more, 1.20 or more, 1.25 or more, 1.30 or more, 1.35 or more, or 1.40 or more, and may be 1.50 or less.

[0122] According to the present invention, a may be 0 or more, and may be 0.20 or less, 0.25 or less, 0.30 or less, 0.35 or less, 0.40 or less, 0.45 or less, or 0.50 or less.

[0123] According to the present invention, b may be 0 or more, and may be 0.05 or less, 0.10 or less, 0.15 or less, or 0.20 or less.

[0124] According to the present invention, Formula 1 may be the following Formula 2 or Formula 3.

[0125] [Formula 2]

[0126] Li 7-(x2+y2) PS 6-(x2+y2) Cl x2 Br y2

[0127] In formula 2,

[0128] 0.1≤x2≤1.4, 0.1≤y2≤1.4 and 1.1 <x2+y2≤1.5。

[0129] [Formula 3]

[0130] Li 7-(x3+y3)+((a3×(5-p’))+(b3×(5-q’))) P 1-(a3+b3) M a3 N b3 S 6-(x3+y3) Cl x3 Br y3

[0131] In formula 3,

[0132] M is at least one selected from Si and Ge,

[0133] N is at least one selected from Sn, Sb, Al, Ga, Zn, Zr, In, and Cu,

[0134] P’ is the oxidation number of M, q’ is the oxidation number of N, and

[0135] 0.1 ≤ x3 ≤ 1.4, 0.1 ≤ y3 ≤ 1.4, 1.1 < x3 + y3 ≤ 1.5, 0 < a3 ≤ 0.5 and 0 < b3 ≤ 0.2.

[0136] According to the present invention, x2 and x3 can each independently be 0.10 or more, 0.15 or more, 0.20 or more, 0.25 or more, 0.30 or more, 0.35 or more, or 0.40 or more, and can be 1.0 or less, 1.05 or less, 1.10 or less, 1.15 or less, 1.20 or less, 1.25 or less, 1.30 or less, 1.35 or less, or 1.40 or less.

[0137] According to the present invention, y2 and y3 can each independently be 0.1 or more, 0.15 or more, 0.20 or more, 0.25 or more, 0.30 or more, 0.35 or more, 0.40 or more, 0.45 or more, or 0.50 or more, and can be 1.0 or less, 1.05 or less, 1.10 or less, 1.15 or less, 1.20 or less, 1.25 or less, 1.30 or less, 1.35 or less, or 1.40 or less.

[0138] According to the present invention, x2 + y2 and x3 + y3 can each independently be 1.10 or more, 1.15 or more, 1.20 or more, 1.25 or more, 1.30 or more, 1.35 or more, or 1.40 or more, and can be 1.50 or less.

[0139] According to the present invention, a3 can be greater than 0, 0.05 or more, 0.10 or more, or 0.15 or more, and can be 0.25 or less, 0.30 or less, 0.35 or less, 0.40 or less, 0.45 or less, or 0.50 or less.

[0140] According to the present invention, b3 can be greater than 0, 0.01 or more, 0.02 or more, or 0.03 or more, and can be 0.07 or less, 0.08 or less, 0.09 or less, 0.10 or less, 0.15 or less, or 0.20 or less.

[0141] The present invention provides a sulfide-based solid electrolyte having a composition represented by the following formula 1 and having a total impurity content of 3 wt % or less. The sulfide-based solid electrolyte according to the present invention can be prepared according to the above-mentioned method for preparing a sulfide-based solid electrolyte, and accordingly, the total impurity content can be small.

[0142] In the case where the sulfide-based solid electrolyte according to the present invention has a composition represented by Formula 2, the total content of impurities may be 3 wt % or less, specifically 2 wt % or less. In addition, in the case where the sulfide-based solid electrolyte according to the present invention has a composition represented by Formula 3, the total content of impurities may be 3 wt % or less.

[0143] According to the present invention, the sulfide-based solid electrolyte may have an ion conductivity of 4.0 mS / cm or more. The ion conductivity of the sulfide-based solid electrolyte may be 4.0 mS / cm or more, 4.1 mS / cm or more, 4.2 mS / cm or more, 4.3 mS / cm or more, 4.4 mS / cm or more, 4.5 mS / cm or more, 4.6 mS / cm or more, 4.7 mS / cm or more, 4.8 mS / cm or more, 4.9 mS / cm or more, 5.0 mS / cm or more, 5.1 mS / cm or more, 5.2 mS / cm or more, 5.3 mS / cm or more, 5.4 mS / cm or more, 5.5 mS / cm or more, 5.6 mS / cm or more, 5.7 mS / cm or more, 5.8 mS / cm or more, 5.9 mS / cm or more, or 6.0 mS / cm or more. The ion conductivity may be when the average particle size (D 50 ) is within the range of 1.0 μm to 5.0 μm. The higher the ionic conductivity, the better, but the upper limit of the ionic conductivity of the sulfide-based solid electrolyte according to the present invention may be 8.0 mS / cm or less, 8.5 mS / cm or less, 9.0 mS / cm or less, 9.5 mS / cm or less, or 10.0 mS / cm or less.

[0144] In the case where the sulfide-based solid electrolyte according to the present invention has a composition represented by Formula 2, the ion conductivity of the solid electrolyte may be 4.0 mS / cm or more, specifically 5.0 mS / cm or more or 6.0 mS / cm or more. In addition, in the case where the sulfide-based solid electrolyte according to the present invention has a composition represented by Formula 3, the ion conductivity of the solid electrolyte may be 4.0 mS / cm or more, specifically 5.0 mS / cm or more, 6.0 mS / cm or more, or 6.5 mS / cm or more.

[0145] According to the present invention, the sulfide-based solid electrolyte may have a -9 mS / cm to 1.0×10 -4 The electronic conductivity of the sulfide-based solid electrolyte can be specifically 1.0×10 -9 mS / cm or more, 0.5×10 -8 mS / cm or more, 1.0×10 -8 mS / cm or more, 0.5×10 -7 mS / cm or more, 1.0×10 -7 mS / cm or more, 2.0×10 -7 mS / cm or above or 3.0×10 -7 mS / cm or more, and can be 7.5×10 -5 mS / cm or less, 8.0×10 -5 ms / cm or less, 8.5×10 -5 mS / cm or less, 9.0×10 -5 mS / cm or less, 9.5×10 -5 mS / cm or less or 1.0×10 -4 In the case where the electronic conductivity of the sulfide-based solid electrolyte is within the above range, since the solid electrolyte blocks the movement of electrons in the solid electrolyte layer and allows only the movement of lithium ions, the solid electrolyte can appropriately function as a solid electrolyte.

[0146] According to the present invention, the sulfide-based solid electrolyte may have an average particle size (D 50 ), specifically 1.0 μm or more, 1.1 μm or more, 1.2 μm or more, 1.3 μm or more, 1.4 μm or more, 1.5 μm or more, 1.6 μm or more, 1.7 μm or more, 1.8 μm or more, 1.9 μm or more, 2.0 μm or more, 2.1 μm or more, 2.2 μm or more, 2.3 μm or more, 2.4 μm or more, or 2.5 μm or more, and 3.5 μm or less, 3.6 μm or less, 3.7 μm or less, 3.8 μm or less, 3.9 μm or less, 4.0 μm or less, 4.1 μm or less, 4.2 μm or less, 4.3 μm or less, 4.4 μm or less, 4.5 μm or less, 4.6 μm or less, 4.7 μm or less, 4.8 μm or less, 4.9 μm or less, or 5.0 μm or less. The average particle size (D 50) In the case where the above range is reached, when a layer is formed by using the solid electrolyte, the layer can be well and uniformly formed, and the resistance of the layer can also be sufficient for the operation of an all-solid-state battery.

[0147] All-solid-state battery

[0148] The present invention provides an all-solid-state battery comprising the above-mentioned sulfide-based solid electrolyte.

[0149] According to one embodiment of the present invention, the all-solid-state battery includes: a positive electrode including a positive electrode active material, a negative electrode including a negative electrode active material, and a solid electrolyte layer arranged between the positive electrode and the negative electrode, and the solid electrolyte layer includes the sulfide-based solid electrolyte.

[0150] Since the all-solid-state battery according to the present invention has a small decrease in ion conductivity due to moisture, the initial efficiency, life characteristics, and output characteristics of the battery may be excellent.

[0151] In this case, the all-solid-state battery of the present invention can be prepared according to a typical method known in the art. For example, the all-solid-state battery of the present invention can be prepared by stacking and pressing so that a solid electrolyte layer exists between the positive electrode and the negative electrode.

[0152] (1) Positive electrode

[0153] The positive electrode may be prepared by coating a positive electrode current collector with a positive electrode slurry including a positive electrode active material, a binder, a conductive material, and a solvent.

[0154] The positive electrode current collector is not particularly limited as long as it has conductivity and does not cause adverse chemical changes in the battery, and for example, stainless steel, aluminum, nickel, titanium, fired carbon, or aluminum or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc. can be used. In addition, fine concavoconvexo can be formed on its surface to improve the bonding strength with the positive electrode active material, and the positive electrode current collector can be used in various shapes such as a film, a sheet, a foil, a mesh, a porous body, a foamed body, a non-woven fabric body, etc.

[0155] The positive electrode active material is a compound capable of reversibly inserting and deinserting lithium, wherein the positive electrode active material may specifically include a lithium metal oxide, wherein the lithium metal oxide includes lithium and at least one metal such as cobalt, manganese, nickel or aluminum. More specifically, the lithium metal oxide may include a lithium manganese oxide (e.g., LiMnO2, LiMn2O4, etc.), a lithium cobalt oxide (e.g., LiCoO2, etc.), a lithium nickel oxide (e.g., LiNiO2, etc.), a lithium nickel manganese oxide (e.g., LiNi 1- Y MnY O2 (where 0 < Y < 1), LiMn 2-Z Ni z O4 (where 0 < Z < 2), etc., lithium nickel cobalt oxides (e.g., LiNi 1-Y1 Co Y1 O2 (where 0 ≤ Y1 < 1), etc., lithium manganese cobalt oxides (e.g., LiCo 1-Y2 Mn Y2 O2 (where 0 < Y2 < 1), LiMn 2-Z1 Co z1 O4 (where 0 < Z1 < 2), etc., lithium nickel manganese cobalt oxides (e.g., Li(Ni p Co q Mn r1 )O2 (where 0 < p < 1, 0 < q < 1, 0 < r1 < 1 and p + q + r1 = 1) or Li(Ni p1 co q1 Mn r2 )O4 (where 0 < p1 < 2, 0 < q1 < 2, 0 < r2 < 2 and p1 + q1 + r2 = 2), etc., or lithium nickel cobalt transition metal (M) oxides (e.g., Li(Ni p2 Co q2 Mn r3 M S2 )O2 (where M is selected from the group consisting of aluminum (Al), iron (Fe), vanadium (V), chromium (Cr), titanium (Ti), tantalum (Ta), magnesium (Mg) and molybdenum (Mo), and p2, q2, r3 and s2 are atomic fractions of respective independent elements, where 0 < p2 < 1, 0 < q2 < 1, 0 < r3 < 1, 0 < s2 < 1 and p2 + q2 + r3 + s2 = 1), and may include any one of them or a mixture of two or more thereof.

[0156] Among these materials, in terms of improving the capacity characteristics and stability of the battery, the lithium metal oxide can be LiCoO2, LiMnO2, LiNiO2, lithium nickel manganese cobalt oxide (e.g., Li(Ni 1 / 3 Mn 1 / 3 Co 1 / 3 )O2, Li(Ni 0.6 Mn 0.2 Co 0.2 )O2, Li(Ni 0.5 Mn 0.3 Co 0.2 )O2, Li(Ni 0.7 Mn 0.15 Co 0.15 )O2 and Li(Ni 0.8 Mn 0.1 Co 0.1)O2, etc.) or lithium nickel cobalt aluminum oxide (e.g., LiNi 0.8 Co 0.15 Al 0.05 O2, etc.), and considering the significant improvement effect caused by controlling the types and content ratios of the components constituting the lithium composite metal oxide, the lithium composite metal oxide may be Li(Ni 0.6 Mn 0.2 Co 0.2 )O2、Li(Ni 0.5 Mn 0.3 Co 0.2 )O2、Li(Ni 0.7 Mn 0.15 Co 0.15 )O2 and Li(Ni 0.8 Mn 0.1 Co 0.1 )O2, and any one of them or a mixture of two or more thereof may be used.

[0157] The positive electrode active material may be contained in an amount of 60 wt % or more, 70 wt % or more and 80 wt % or less, or 99 wt % or less and 98 wt % or less based on the total weight of the solid content excluding the solvent in the positive electrode slurry.

[0158] The binder is a component that helps to bind the conductive material, the active material and the current collector. Examples of the binder may be polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer, sulfonated ethylene-propylene-diene monomer, styrene-butadiene rubber, fluororubber, or various copolymers thereof.

[0159] The content of the binder is generally 1 to 20 wt %, preferably 1 to 15 wt %, and more preferably 1 to 10 wt %, based on the total weight of the solid content excluding the solvent in the positive electrode slurry.

[0160] The conductive material is a component for further improving the conductivity of the positive electrode active material.

[0161] The conductive material is not particularly limited as long as it has conductivity and does not cause adverse chemical changes in the battery, and for example, a conductive material such as graphite; a carbon-based material such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black or thermal black; conductive fibers such as carbon fibers or metal fibers; fluorocarbon powder; metal powder such as aluminum powder and nickel powder; conductive whiskers such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides such as titanium oxide; or polyphenylene derivatives can be used.

[0162] The content of the conductive material may generally be 1 wt % or more, 20 wt % or less, 15 wt % or less, and 10 wt % or less based on the total weight of the solid content excluding the solvent in the positive electrode slurry.

[0163] The solvent may include an organic solvent, such as N-methyl-2-pyrrolidone (NMP), and may be used in an amount to obtain a desired viscosity when the positive electrode active material and the optional binder and the conductive material are included. For example, the content of the solvent may be such that the concentration of the solid content including the positive electrode active material and the optional binder and the conductive material is 50% by weight or more, 60% by weight or more, 70% by weight or more, 95% by weight or less, 90% by weight or less, and 85% by weight or less.

[0164] (2) Negative electrode

[0165] For example, the negative electrode may be prepared by coating a negative electrode slurry including a negative electrode active material, a binder, a conductive material, and a solvent on a negative electrode collector, or a graphite electrode formed of carbon (C) or lithium metal itself having a thickness of 50 μm or less may be used as the negative electrode.

[0166] For example, in the case where the negative electrode is prepared by coating the negative electrode slurry on the negative electrode collector, the negative electrode collector generally has a thickness of 3 μm to 500 μm. The negative electrode collector is not particularly limited as long as it has high conductivity and does not cause adverse chemical changes in the battery, and for example, copper, stainless steel, aluminum, nickel, titanium, fired carbon, copper or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. can be used. Moreover, similar to the positive electrode collector, the negative electrode collector may have a fine surface roughness to improve the bonding strength with the negative electrode active material, and the negative electrode collector may be used in various shapes such as films, sheets, foils, nets, porous bodies, foams, non-woven fabrics, etc.

[0167] The negative electrode active material may include at least one negative electrode active material selected from the group consisting of natural graphite, artificial graphite, carbonaceous materials; lithium-containing titanium composite oxide (LTO), Si, SiO x , metal (Me) such as Sn, Li, Zn, Mg, cadmium (Cd), cerium (Ce), nickel (Ni) or Fe; alloys composed of metal (Me); oxides of metal (Me) (MeO x ); and a composite material of metal (Me) and carbon. Specifically, a composite material containing silicon (Si), silicon oxide (SiO x) or a silicon-based negative electrode active material of a silicon alloy as the negative electrode active material. In this case, since a thin and stable SEI layer containing a siloxane bond is formed, the high temperature stability and life characteristics of the battery can be further improved.

[0168] The negative electrode active material may be contained in an amount of 60 wt % or more, 70 wt % or more, 80 wt % or more, 99 wt % or less, and 98 wt % or less based on the total weight of the solid content excluding the solvent in the negative electrode slurry.

[0169] The binder is a component that helps to bind the conductive material, the active material and the current collector. Examples of the binder may be polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer, sulfonated ethylene-propylene-diene monomer, styrene-butadiene rubber, fluororubber, or various copolymers thereof.

[0170] The content of the binder may generally be 1 wt % or more, 20 wt % or less, 15 wt % or less, and 10 wt % or less based on the total weight of the solid content excluding the solvent in the negative electrode slurry.

[0171] The conductive material is a component for further improving the conductivity of the negative electrode active material. The conductive material is not particularly limited as long as it has conductivity and does not cause adverse chemical changes in the battery, and for example, conductive materials such as: graphite, such as natural graphite or artificial graphite; carbon black, such as acetylene black, Ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers, such as carbon fibers or metal fibers; fluorocarbon powder; metal powder, such as aluminum powder and nickel powder; conductive whiskers, such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides, such as titanium oxide; or polyphenylene derivatives.

[0172] The content of the conductive material may be 1 wt % or more, 20 wt % or less, 15 wt % or less, and 10 wt % or less based on the total weight of the solid content excluding the solvent in the negative electrode slurry.

[0173] The solvent may include water or an organic solvent, such as N-methyl-2-pyrrolidone (NMP), and may be used in an amount to obtain a desired viscosity when the negative electrode active material and the optional binder and the conductive material are included. For example, the content of the solvent may be such that the concentration of the solid content including the negative electrode active material and the optional binder and the conductive material is 50% by weight or more, 60% by weight or more, 70% by weight or more, 95% by weight or less, 90% by weight or less, and 85% by weight or less.

[0174] In the case where a metal itself is used as the negative electrode, the negative electrode may be a metal film itself, or may be prepared by a method in which a metal is physically bonded, rolled, or deposited on the negative electrode current collector. As a deposition method, an electrodeposition method or a chemical vapor deposition method for a metal may be used.

[0175] For example, the metal film itself or the metal to be bonded / rolled / deposited on the negative electrode current collector may contain one type of metal selected from the group consisting of lithium (Li), nickel (Ni), tin (Sn), copper (Cu) and indium (In), or an alloy of two types of metals.

[0176] (3) Solid electrolyte layer

[0177] The solid electrolyte layer may further contain a binder in addition to the sulfide-based solid electrolyte according to the present invention.

[0178] The binder is a component that helps to bind the conductive material, the active material and the current collector. Examples of the binder may be polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer, sulfonated ethylene-propylene-diene monomer, styrene-butadiene rubber, fluororubber, or various copolymers thereof.

[0179] The content of the binder may be 1 wt % or more, 20 wt % or less, 15 wt % or less, and 10 wt % or less, based on the total weight of the solid electrolyte layer.

[0180] The present invention provides a battery module including the all-solid-state battery as a unit cell, and can provide a battery pack including the battery module. Since the battery module and the battery pack include the secondary battery having high capacity, high rate capability and high cycle characteristics, the battery module and the battery pack can be used as a power source for medium and large devices selected from the group consisting of: electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and power storage systems.

[0181] Hereinafter, embodiments of the present invention will be described in detail in a manner that can be easily implemented by those skilled in the art to which the present invention belongs. However, the present invention can be implemented in many different ways and should not be construed as being limited to the embodiments set forth herein.

[0182] Examples and Comparative Examples

[0183] Example 1

[0184] Li2S powder, P2S5 powder, LiCl powder and LiBr powder were prepared respectively. The Li2S powder, P2S5 powder, LiCl powder and LiBr powder were pre-crushed using a planetary ball mill (FRITSCH GmbH, PULVERISETTE 7 Planetary Micro Mill-Premium line). In this case, zirconia balls with a diameter of 1 mm and zirconia balls with a diameter of 3 mm were added to the zirconia container of the planetary ball mill in a weight ratio of 1:1 and each powder was added so that the BPR (ball to powder ratio) was 6, and then pre-crushed at 550 rpm for 2 hours.

[0185] Thereafter, zirconia balls with a diameter of 3 mm and zirconia balls with a diameter of 5 mm were added to the zirconia container of the planetary ball mill (FRITSCH GmbH, PULVERISETTE 7 Planetary Micro Mill-Premiumline) in a weight ratio of 1:1, and pre-crushed Li2S powder, P2S5 powder, LiCl powder and LiBr powder were added in a certain proportion so that the composition of the obtained solid electrolyte was Li 5.5 PS 4.5 ClBr 0.5 And the BPR was 6, xylene was added in an amount of 2.5 wt % based on the total amount of the Li 2 S powder, P 2 S 5 powder, LiCl powder and LiBr powder, and then a reaction mixture was prepared by mixing them at 300 rpm for 4 hours.

[0186] Thereafter, after the reaction mixture was placed in a vacuum oven and vacuum dried at 80° C. for 4 hours, 5 g of the powder was compressed into a pellet form at 200 MPa using a die having a diameter of 25 mm and a press.

[0187] Thereafter, the pelletized reaction mixture was sintered at 550° C. in an argon atmosphere to prepare a sintered product. Furthermore, the sintered product was pulverized with an agate mortar and pestle for 30 minutes and then pulverized using a planetary ball mill (FRITSCH GmbH, PULVERISETTE 7 Planetary Micro Mill-Premium line) to prepare a sulfide-based solid electrolyte (composition: Li 5.5 PS 4.5 ClBr 0.5). In this case, regarding the above-mentioned pulverization, after adding zirconia balls having a diameter of 3 mm and zirconia balls having a diameter of 5 mm in a weight ratio of 1:1 to the zirconia container of the planetary ball mill apparatus and adding the sintered product pulverized in a mortar so that the BPR is 6, pulverizing at 250 rpm for 10 minutes and standing for 20 minutes was set as one cycle, and the cycle was repeated 20 times.

[0188] Example 2

[0189] A sulfide-based solid electrolyte (composition: Li 5.5 PS 4.5 ClBr 0.5 ), except that the pre-crushing was carried out at a rotation speed of 650 rpm instead of 550 rpm.

[0190] Example 3

[0191] A sulfide-based solid electrolyte (composition: Li 5.5 PS 4.5 ClBr 0.5 ), except that xylene was added in an amount of 3.5 wt % instead of 2.5 wt % based on the total amount of the Li2S powder, P2S5 powder, LiCl powder and LiBr powder.

[0192] Example 4

[0193] A sulfide-based solid electrolyte (composition: Li 5.5 PS 4.5 ClBr 0.5 ), except that xylene was added in an amount of 6.0 wt % instead of 2.5 wt % based on the total amount of the Li2S powder, P2S5 powder, LiCl powder and LiBr powder.

[0194] Example 5

[0195] Li2S powder, P2S5 powder, LiCl powder, LiBr powder, SiS2 powder and SnS2 powder were prepared respectively. The Li2S powder, P2S5 powder, LiCl powder, LiBr powder, SiS2 powder and SnS2 powder were pre-crushed using a planetary ball mill (FRITSCH GmbH, PULVERISETTE 7 Planetary Micro Mill-Premium line). In this case, a zirconia ball with a diameter of 1 mm and a zirconia ball with a diameter of 3 mm were added to the zirconia container of the planetary ball mill in a weight ratio of 1:1 and each powder was added so that the BPR was 6, and then pre-crushed at 550 rpm for 2 hours.

[0196] Thereafter, zirconia balls with a diameter of 3 mm and zirconia balls with a diameter of 5 mm were added to the zirconia container of the planetary ball mill (FRITSCH GmbH, PULVERISETTE 7 Planetary Micro Mill-Premiumline) in a weight ratio of 1:1, and pre-crushed Li2S powder, P2S5 powder, LiCl powder, LiBr powder, SiS2 powder and SnS2 powder were added in a certain proportion so that the composition of the obtained solid electrolyte was Li 5.85 Si 0.2 Sn 0.05 P 0.75 S 4.6 Cl 0.4 Br and a BPR of 6, xylene was added in an amount of 2.5 wt % based on the total amount of the Li2S powder, P2S5 powder, LiCl powder, LiBr powder, SiS2 powder and SnS2 powder, and then a reaction mixture was prepared by mixing them at 300 rpm for 4 hours.

[0197] Thereafter, after the reaction mixture was placed in a vacuum oven and vacuum dried at 80° C. for 4 hours, 5 g of the powder was compressed into a pellet form at 100 MPa using a die having a diameter of 25 mm and a press.

[0198] Thereafter, the pelletized reaction mixture was sintered at 450° C. in an argon atmosphere to prepare a sintered product. Furthermore, the sintered product was pulverized with an agate mortar and pestle for 30 minutes and then pulverized using a planetary ball mill (FRITSCH GmbH, PULVERISETTE 7 Planetary Micro Mill-Premium line) to prepare a sulfide-based solid electrolyte (composition: Li 5.85 Si 0.2 Sn0.05 P 0.75 S 4.6 Cl 0.4 Br). In this case, regarding the above-mentioned pulverization, after adding zirconia balls having a diameter of 3 mm and zirconia balls having a diameter of 5 mm in a weight ratio of 1:1 to the zirconia container of the planetary ball mill apparatus and adding the sintered product pulverized by a mortar so that the BPR is 6, pulverization at 250 rpm for 10 minutes and standing for 20 minutes was set as one cycle, and the cycle was repeated 20 times.

[0199] Example 6

[0200] A sulfide-based solid electrolyte (composition: Li 5.85 Si 0.2 Sn 0.05 P 0.7 5S 4.6 Cl 0.4 Br), except that the pre-crushing was carried out at a rotation speed of 650 rpm instead of 550 rpm.

[0201] Example 7

[0202] A sulfide-based solid electrolyte (composition: Li 5.85 Si 0.2 Sn 0.05 P 0.7 5S 4.6 Cl 0.4 Br), except that xylene was added in an amount of 3.5 wt % instead of 2.5 wt % based on the total amount of the Li2S powder, P2S5 powder, LiCl powder, LiBr powder, SiS2 powder and SnS2 powder.

[0203] Example 8

[0204] A sulfide-based solid electrolyte (composition: Li 5.85 Si 0.2 Sn 0.05 P 0.7 5S 4.6 Cl 0.4 Br), except that xylene was added in an amount of 6.0 wt % instead of 2.5 wt % based on the total amount of the Li 2 S powder, P 2 S 5 powder, LiCl powder, LiBr powder, SiS 2 powder and SnS 2 powder.

[0205] Example 9

[0206] Li2S powder, P2S5 powder and LiCl powder were prepared respectively. The Li2S powder, P2S5 powder and LiCl powder were pre-crushed using a planetary ball mill (FRITSCH GmbH, PULVERISETTE 7 Planetary Micro Mill-Premium line). In this case, zirconia balls with a diameter of 1 mm and zirconia balls with a diameter of 3 mm were added to the zirconia container of the planetary ball mill at a weight ratio of 1:1 and each powder was added so that the BPR was 6, and then pre-crushed at 550 rpm for 2 hours.

[0207] Thereafter, zirconia balls having a diameter of 3 mm and zirconia balls having a diameter of 5 mm were added to the zirconia container of the planetary ball mill equipment (FRITSCH GmbH, PULVERISETTE 7 Planetary Micro Mill-Premiumline) in a weight ratio of 1:1, pre-crushed Li2S powder, P2S5 powder and LiCl powder were added in a certain proportion so that the composition of the obtained solid electrolyte was Li6PS5Cl and the BPR was 6, xylene was added in an amount of 2.5 wt % based on the total amount of the Li2S powder, P2S5 powder and LiCl powder, and then a reaction mixture was prepared by mixing them at 300 rpm for 4 hours.

[0208] Thereafter, after the reaction mixture was placed in a vacuum oven and vacuum dried at 80° C. for 4 hours, 5 g of the powder was compressed into a pellet form at 200 MPa using a die having a diameter of 25 mm and a press.

[0209] Thereafter, the pellet-shaped reaction mixture was sintered at 550°C in an argon atmosphere to prepare a sintered product. In addition, the sintered product was crushed with an agate mortar and pestle for 30 minutes, and then crushed using the planetary ball mill device (FRITSCH GmbH, PULVERISETTE 7 Planetary Micro Mill-Premium line) to prepare a sulfide-based solid electrolyte (composition: Li6PS5Cl). In this case, regarding the above-mentioned crushing, after adding a zirconia ball with a diameter of 3 mm and a zirconia ball with a diameter of 5 mm to the zirconia container of the planetary ball mill device in a weight ratio of 1:1 and adding the sintered product crushed in the mortar so that the BPR is 6, crushing at 250 rpm for 10 minutes and standing for 20 minutes is set as one cycle, and 20 cycles are repeated.

[0210] Comparative Example 1

[0211] Li2S powder, P2S5 powder, LiCl powder and LiBr powder were prepared respectively. Zirconia balls with a diameter of 3 mm were added to the zirconium oxide container of a planetary ball mill (FRITSCH GmbH, PULVERISETTE 7 Planetary Micro Mill-Premiumline), and the Li2S powder, P2S5 powder, LiCl powder and LiBr powder were added in a certain proportion so that the composition of the obtained solid electrolyte was Li 5.5 PS 4.5 ClBr 0.5 and the BPR was 6, and then a reaction mixture was prepared by mixing them at 300 rpm for 4 hours.

[0212] Thereafter, the reaction mixture was sintered at 550° C. in an argon atmosphere to prepare a sintered product. Furthermore, the sintered product was pulverized with an agate mortar and pestle for 30 minutes and then pulverized using the planetary ball mill apparatus (FRITSCH GmbH, PULVERISETTE 7 Planetary Micro Mill-Premium line) to prepare a sulfide-based solid electrolyte (composition: Li 5.5 PS 4.5 ClBr 0.5 ). In this case, regarding the above-mentioned pulverization, after adding zirconia balls having a diameter of 3 mm and zirconia balls having a diameter of 5 mm in a weight ratio of 1:1 to the zirconia container of the planetary ball mill apparatus and adding the sintered product pulverized in a mortar so that the BPR is 6, pulverizing at 250 rpm for 10 minutes and standing for 20 minutes was set as one cycle, and the cycle was repeated 20 times.

[0213] Comparative Example 2

[0214] Li2S powder, P2S5 powder, LiCl powder and LiBr powder were prepared respectively. Zirconia balls with a diameter of 3 mm and 5 mm were added to a zirconia container of a planetary ball mill (FRITSCH GmbH, PULVERISETTE 7 Planetary Micro Mill-Premium line) in a weight ratio of 1:1, and the Li2S powder, P2S5 powder, LiCl powder and LiBr powder were added in a certain proportion so that the composition of the obtained solid electrolyte was Li 5.5 PS 4.5 ClBr 0.5And the BPR was 6, xylene was added in an amount of 2.5 wt % based on the total amount of the Li 2 S powder, P 2 S 5 powder, LiCl powder and LiBr powder, and then a reaction mixture was prepared by mixing them at 300 rpm for 4 hours.

[0215] Thereafter, after the reaction mixture was placed in a vacuum oven and vacuum dried at 80° C. for 4 hours, 5 g of the powder was compressed into a pellet form at 200 MPa using a die having a diameter of 25 mm and a press.

[0216] Thereafter, the pelletized reaction mixture was sintered at 550° C. in an argon atmosphere to prepare a sintered product. Furthermore, the sintered product was pulverized with an agate mortar and pestle for 30 minutes and then pulverized using a planetary ball mill (FRITSCH GmbH, PULVERISETTE 7 Planetary Micro Mill-Premium line) to prepare a sulfide-based solid electrolyte (composition: Li 5.5 PS 4.5 ClBr 0.5 ). In this case, regarding the above-mentioned pulverization, after adding zirconia balls having a diameter of 3 mm and zirconia balls having a diameter of 5 mm in a weight ratio of 1:1 to the zirconia container of the planetary ball mill apparatus and adding the sintered product pulverized in a mortar so that the BPR is 6, pulverizing at 250 rpm for 10 minutes and standing for 20 minutes was set as one cycle, and the cycle was repeated 20 times.

[0217] Comparative Example 3

[0218] Li2S powder, P2S5 powder, LiCl powder and LiBr powder were prepared respectively. The Li2S powder, P2S5 powder, LiCl powder and LiBr powder were pre-crushed using a planetary ball mill (FRITSCH GmbH, PULVERISETTE 7 Planetary Micro Mill-Premium line). In this case, zirconia balls with a diameter of 1 mm and zirconia balls with a diameter of 3 mm were added to the zirconia container of the planetary ball mill in a weight ratio of 1:1 and each powder was added so that the BPR (ball to powder ratio) was 6, and then pre-crushed at 550 rpm for 2 hours.

[0219] Thereafter, zirconia balls with a diameter of 3 mm and zirconia balls with a diameter of 5 mm were added to the zirconia container of the planetary ball mill (FRITSCH GmbH, PULVERISETTE 7 Planetary Micro Mill-Premiumline) in a weight ratio of 1:1, and pre-crushed Li2S powder, P2S5 powder, LiCl powder and LiBr powder were added in a certain proportion so that the composition of the obtained solid electrolyte was Li 5.5 PS 4.5 ClBr 0.5 And the BPR was 6, xylene was added in an amount of 2.5 wt % based on the total amount of the Li 2 S powder, P 2 S 5 powder, LiCl powder and LiBr powder, and then a reaction mixture was prepared by mixing them at 300 rpm for 4 hours.

[0220] Thereafter, the reaction mixture was sintered at 550° C. in an argon atmosphere to prepare a sintered product. Furthermore, the sintered product was pulverized with an agate mortar and pestle for 30 minutes and then pulverized using the planetary ball mill apparatus (FRITSCH GmbH, PULVERISETTE 7 Planetary Micro Mill-Premium line) to prepare a sulfide-based solid electrolyte (composition: Li 5.5 PS 4.5 ClBr 0.5 ). In this case, regarding the above-mentioned pulverization, after adding zirconia balls having a diameter of 3 mm and zirconia balls having a diameter of 5 mm in a weight ratio of 1:1 to the zirconia container of the planetary ball mill apparatus and adding the sintered product pulverized in a mortar so that the BPR is 6, pulverizing at 250 rpm for 10 minutes and standing for 20 minutes was set as one cycle, and the cycle was repeated 20 times.

[0221] Comparative Example 4

[0222] Li2S powder, P2S5 powder, LiCl powder, LiBr powder, SiS2 powder and SnS2 powder were prepared respectively. Zirconia balls with a diameter of 3 mm were added to the zirconium oxide container of a planetary ball mill (FRITSCH GmbH, PULVERISETTE 7 PlanetaryMicro Mill-Premium line), and the Li2S powder, P2S5 powder, LiCl powder, LiBr powder, SiS2 powder and SnS2 powder were added in a certain proportion so that the composition of the obtained solid electrolyte was Li 5.85 Si 0.2 Sn 0.0 5P 0.75 S4.6 Cl 0.4 Br and a BPR of 6, and then a reaction mixture was prepared by mixing them at 300 rpm for 4 hours.

[0223] Thereafter, the reaction mixture was sintered at 550° C. in an argon atmosphere to prepare a sintered product. Furthermore, the sintered product was pulverized with an agate mortar and pestle for 30 minutes and then pulverized using the planetary ball mill apparatus (FRITSCH GmbH, PULVERISETTE 7 Planetary Micro Mill-Premium line) to prepare a sulfide-based solid electrolyte (composition: Li 5.85 Si 0.2 Sn 0.05 P 0.75 S 4. 6Cl 0.4 Br). In this case, regarding the above-mentioned pulverization, after adding zirconia balls having a diameter of 3 mm and zirconia balls having a diameter of 5 mm in a weight ratio of 1:1 to the zirconia container of the planetary ball mill apparatus and adding the sintered product pulverized by a mortar so that the BPR is 6, pulverization at 250 rpm for 10 minutes and standing for 20 minutes was set as one cycle, and the cycle was repeated 20 times.

[0224] Comparative Example 5

[0225] Li2S powder, P2S5 powder, LiCl powder, LiBr powder, SiS2 powder and SnS2 powder were prepared respectively. Zirconia balls with a diameter of 3 mm and 5 mm were added to a zirconia container of a planetary ball mill (FRITSCH GmbH, PULVERISETTE 7 Planetary Micro Mill-Premium line) in a weight ratio of 1:1, and the Li2S powder, P2S5 powder, LiCl powder, LiBr powder, SiS2 powder and SnS2 powder were added in a certain proportion so that the composition of the obtained solid electrolyte was Li 5.85 Si 0.2 Sn 0.05 P 0.75 S 4.6 Cl 0.4 Br and a BPR of 6, xylene was added in an amount of 2.5 wt % based on the total amount of the Li2S powder, P2S5 powder, LiCl powder, LiBr powder, SiS2 powder and SnS2 powder, and then a reaction mixture was prepared by mixing them at 300 rpm for 4 hours.

[0226] Thereafter, after the reaction mixture was placed in a vacuum oven and vacuum dried at 80° C. for 4 hours, 5 g of the powder was compressed into a pellet form at 100 MPa using a die having a diameter of 25 mm and a press.

[0227] Thereafter, the pelletized reaction mixture was sintered at 550° C. in an argon atmosphere to prepare a sintered product. Furthermore, the sintered product was pulverized with an agate mortar and pestle for 30 minutes and then pulverized using a planetary ball mill (FRITSCH GmbH, PULVERISETTE 7 Planetary Micro Mill-Premium line) to prepare a sulfide-based solid electrolyte (composition: Li 5.85 Si 0.2 Sn 0.05 P 0.75 S 4.6 Cl 0.4 Br). In this case, regarding the above-mentioned pulverization, after adding zirconia balls having a diameter of 3 mm and zirconia balls having a diameter of 5 mm in a weight ratio of 1:1 to the zirconia container of the planetary ball mill apparatus and adding the sintered product pulverized by a mortar so that the BPR is 6, pulverization at 250 rpm for 10 minutes and standing for 20 minutes was set as one cycle, and the cycle was repeated 20 times.

[0228] Comparative Example 6

[0229] Li2S powder, P2S5 powder, LiCl powder, LiBr powder, SiS2 powder and SnS2 powder were prepared respectively. The Li2S powder, P2S5 powder, LiCl powder, LiBr powder, SiS2 powder and SnS2 powder were pre-crushed using a planetary ball mill (FRITSCH GmbH, PULVERISETTE 7 Planetary Micro Mill-Premium line). In this case, a zirconia ball with a diameter of 1 mm and a zirconia ball with a diameter of 3 mm were added to the zirconia container of the planetary ball mill in a weight ratio of 1:1 and each powder was added so that the BPR was 6, and then pre-crushed at 550 rpm for 2 hours.

[0230] Thereafter, zirconia balls with a diameter of 3 mm and zirconia balls with a diameter of 5 mm were added to the zirconia container of the planetary ball mill (FRITSCH GmbH, PULVERISETTE 7 Planetary Micro Mill-Premiumline) in a weight ratio of 1:1, and pre-crushed Li2S powder, P2S5 powder, LiCl powder, LiBr powder, SiS2 powder and SnS2 powder were added in a certain proportion so that the composition of the obtained solid electrolyte was Li 5.85 Si 0.2 Sn 0.05 P 0.75 S 4.6 Cl 0.4 Br and a BPR of 6, xylene was added in an amount of 2.5 wt % based on the total amount of the Li2S powder, P2S5 powder, LiCl powder, LiBr powder, SiS2 powder and SnS2 powder, and then a reaction mixture was prepared by mixing them at 300 rpm for 4 hours.

[0231] Thereafter, the reaction mixture was sintered at 450° C. in an argon atmosphere to prepare a sintered product. Furthermore, the sintered product was pulverized with an agate mortar and pestle for 30 minutes and then pulverized using the planetary ball mill apparatus (FRITSCH GmbH, PULVERISETTE 7 Planetary Micro Mill-Premium line) to prepare a sulfide-based solid electrolyte (composition: Li 5.85 Si 0.2 Sn 0.05 P 0.75 S 4.6 Cl 0.4 Br). In this case, regarding the above-mentioned pulverization, after adding zirconia balls having a diameter of 3 mm and zirconia balls having a diameter of 5 mm in a weight ratio of 1:1 to the zirconia container of the planetary ball mill apparatus and adding the sintered product pulverized by a mortar so that the BPR is 6, pulverization at 250 rpm for 10 minutes and standing for 20 minutes was set as one cycle, and the cycle was repeated 20 times.

[0232] Comparative Example 7

[0233] Li2S powder, P2S5 powder and LiCl powder were prepared separately. Zirconia balls with a diameter of 3 mm were added to the zirconia container of a planetary ball mill (FRITSCH GmbH, PULVERISETTE 7 Planetary Micro Mill-Premium line), the Li2S powder, P2S5 powder and LiCl powder were added in a certain proportion so that the composition of the obtained solid electrolyte was Li6PS5Cl and the BPR was 6, and then a reaction mixture was prepared by mixing them at 300 rpm for 4 hours.

[0234] Thereafter, the reaction mixture was sintered at 550°C in an argon atmosphere to prepare a sintered product. In addition, the sintered product was crushed with an agate mortar and pestle for 30 minutes, and then crushed using the planetary ball mill device (FRITSCH GmbH, PULVERISETTE 7 Planetary Micro Mill-Premium line) to prepare a sulfide-based solid electrolyte (composition: Li6PS5Cl). In this case, regarding the above-mentioned crushing, a zirconia ball with a diameter of 3 mm and a zirconia ball with a diameter of 5 mm were added to the zirconia container of the planetary ball mill device in a weight ratio of 1:1 and the sintered product crushed in the mortar was added so that the BPR was 6, and crushing at 250 rpm for 10 minutes and standing for 20 minutes was set as one cycle, and 20 cycles were repeated.

[0235] Table 1 below shows the compositions of the solid electrolytes prepared in Examples and Comparative Examples, whether the raw materials were pulverized separately before mixing, and whether the reaction mixture was processed into a pellet form.

[0236]

[0237] Experimental example

[0238] Experimental Example 1: Impurity Evaluation

[0239] The impurity ratio of the solid electrolyte powder was calculated using X-ray diffraction (XRD) measurements and Rietveld refinement analysis. Bruker's D8 Endeavor with Cu Kα radiation at a wavelength of 1.5406 Å was used as the XRD equipment, and a scanning rate of 2 degrees / minute and a 2θ angle of 10 to 90 degrees under non-atmospheric exposure were used as measurement conditions. The impurities (Li2S, LiCl, LiBr, and Li4SiS4) were identified using the TOPASRietevld refinement program, and the ratio of the impurities was quantified and presented in Table 2 below.

[0240] Experimental Example 2: Evaluation of ion conductivity

[0241] 150 mg of each solid electrolyte powder prepared in the embodiment and the comparative example was collected and added to a SUS mold with a diameter of 13 mm. A potentiostat (Biologics, SP-200) was connected to the SUS mold in a state where the mold was mounted on a PEEK-insulated press. After the electrolyte structure was fully compacted by pressurizing at 370 MPa, AC impedance measurements were performed at a measurement frequency of 0.1 Hz to 7 MHz while slowly reducing the pressure and maintaining it at 100 MPa. The ionic conductivity was calculated from the measured resistance value by the Nyquist plot and is presented in Table 2 below. All measurements were carried out in a drying chamber at a temperature of 25 ° C and a relative humidity of 0.7%.

[0242] Experimental Example 3: Evaluation of electronic conductivity

[0243] After 150 mg of each solid electrolyte prepared in the examples and comparative examples was added to a mold having a diameter of Φ13 mm and pressurized at 370 MPa to form a solid electrolyte layer, the pressure level was reduced to 100 MPa, and after the current was saturated by applying a DC of 1 V for 6 hours at room temperature (25°C) using a potentiostat (Biologics, SP-200) so that the current did not change, the electronic conductivity was measured by measuring the current value, and the results are presented in Table 2 below.

[0244] Experimental Example 4

[0245] 20 mg of each solid electrolyte powder prepared in the examples and comparative examples was dispersed in 5 ml of xylene and then introduced into a laser diffraction particle size measuring instrument (Mastersizer 3000, Malvern Panalytical Ltd.) to measure the average particle size (D 50 ), and the results are presented in Table 2 below.

[0246]

[0247] Referring to Tables 1 and 2, when preparing a sulfide-based solid electrolyte having the same composition, the raw materials are pre-crushed and then mixed to prepare a reaction mixture, and the reaction mixture is compressed into a pellet form and then sintered, it can be confirmed that the impurity content is significantly reduced. Accordingly, it can be confirmed that the ion conductivity and the electronic conductivity are also improved.

[0248] As a result, it can be understood that the method for preparing a sulfide-based solid electrolyte according to the present invention can not only prevent the adhesion of the raw materials but also improve the reactivity of the raw materials, and, with respect to the sulfide-based solid electrolyte prepared according to the method for preparing a sulfide-based solid electrolyte according to the present invention, since impurities are almost absent, it can be understood that physical properties such as ion conductivity and electron conductivity are excellent.

Claims

1. A method for preparing a sulfide-based solid electrolyte, the method comprising the following steps: (A) preparing a reaction mixture by pulverizing respective sulfide-based solid electrolyte raw materials and mixing the pulverized raw materials; (B) compressing the reaction mixture into a pellet form; and (C) preparing a sintered product by sintering the pellet-shaped reaction mixture.

2. The method according to claim 1, wherein the sulfide-based solid electrolyte raw material comprises: (i) lithium-containing raw materials, (ii) phosphorus-containing raw materials, (iii) a sulfur-containing feedstock, and optionally (iv) at least one selected from a halogen-containing raw material, an M-containing raw material (M is at least one selected from silicon (Si) and germanium (Ge)), and a N-containing raw material (N is at least one selected from tin (Sn), antimony (Sb), aluminum (Al), gallium (Ga), zinc (Zn), zirconium (Zr), indium (In), and copper (Cu)).

3. The method according to claim 1, wherein the pulverization in step (A) is performed by a ball mill using two or more balls having different diameters.

4. The method according to claim 3, wherein: During the pulverization of the step (A), the diameter of the balls is 1 mm, 3 mm or 5 mm. 5 . The method according to claim 1 , wherein the pulverizing in step (A) is performed at a rotation speed of 500 rpm to 800 rpm.

6. The method according to claim 1, wherein the mixing in step (A) is performed by mixing in a ball mill using two or more balls having different diameters.

7. The method according to claim 6, wherein: During the mixing of step (A), the diameter of the spheres is 1 mm, 3 mm, 5 mm or 10 mm.

8. The method according to claim 1, wherein the mixing in step (A) is performed at a rotation speed of 200 rpm to 500 rpm.

9. The method according to claim 2, wherein (iv) the halogen-containing raw material comprises a chlorine-containing raw material and a bromine-containing raw material, and The ratio of the number of moles of halogen contained in the reaction mixture to the total number of moles of phosphorus, M and N is in the range of 1.1 to 1.

5.

10. The method according to claim 1, wherein: During the preparation of the reaction mixture, a non-reactive solvent having a relative polarity of 0 to 0.15 with respect to water is further mixed. 11 . The method according to claim 10 , wherein the non-reactive solvent is mixed in an amount of 2.5 wt % to 5.0 wt % based on the total amount of the sulfide-based solid electrolyte raw material.

12. The method according to claim 1, wherein the compressing of the step (B) is performed at a pressure of 50 MPa to 400 MPa.

13. The method according to claim 1, wherein the sintering is performed at a temperature of 350°C to 600°C.

14. The method according to claim 1, further comprising the steps of: (D) pulverizing the sintered product.

15. The method according to claim 14, wherein the pulverizing in step (D) comprises mortar pulverizing the sintered product, and ball mill pulverizing the mortar pulverized sintered product using two or more balls having different diameters.

16. The method according to claim 15, wherein: During the pulverization in the step (D), the diameter of the balls is 1 mm, 3 mm, 5 mm or 10 mm.

17. The method according to claim 14, wherein the pulverization in the step (D) is carried out at a rotation speed of 100 rpm to 500 rpm.

18. A sulfide-based solid electrolyte having a composition represented by Formula 1 and having a total impurity content of 3 wt% or less: [Formula 1] Li 7-(x+y)+((a×(5-p))+(b×(5-q))) P 1-(a+b) M a N b S 6-(x+y) Cl x Br y in, In Formula 1, M is at least one selected from silicon (Si) and germanium (Ge), N is at least one selected from tin (Sn), antimony (Sb), aluminum (Al), gallium (Ga), zinc (Zn), zirconium (Zr), indium (In) and copper (Cu), p is the oxidation number of M and q is the oxidation number of N, and 0.1 ≤ x ≤ 1.4, 0.1 ≤ y ≤ 1.4, 1.1 < x + y ≤ 1.5, 0 ≤ a ≤ 0.5 and 0 ≤ b ≤ 0.

2.

19. The sulfide-based solid electrolyte according to claim 18, wherein the sulfide-based solid electrolyte has an ionic conductivity of 4.0 mS / cm or more.

20. The sulfide-based solid electrolyte according to claim 18, wherein the sulfide-based solid electrolyte has a -9 mS / cm to 1.0×10 -4 Electronic conductivity in mS / cm.

21. The sulfide-based solid electrolyte according to claim 18, wherein the sulfide-based solid electrolyte has an average particle size (D 50 ).

Citation Information

Patent Citations

  • Method for producing polyester carbonate

    KR1020220117225A

  • Polyester carbonates from aliphatic diacids and aliphatic diols, and methods for producing the same

    KR1020220117226A